PENGUATAN LITERASI DIGITAL SISWA SMK N 5 BEKASI: MENGENAL DAN MENCEGAH MODUS LOWONGAN KERJA PALSU - Saeful Mujab; Metha Madonna; Muhamad Sofyan (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT The increasing prevalence of online job vacancy scams poses a serious challenge for vocational high school students who are in the transitional phase toward entering the workforce. This Community Service Program (PkM) aimed to strengthen the digital literacy of students at SMK Negeri 5 Kota Bekasi so that they are able to independently recognize and prevent fraudulent online job offers. The program was implemented through interactive workshops based on case studies and verification simulations, with evaluation employing a pre- and post-activity design to measure changes in participants’ knowledge, self-efficacy, and verification skills. The results indicate a notable improvement in students’ understanding of scam risk indicators, the reasonableness of recruitment procedures, and the importance of personal data protection, accompanied by the development of more cautious attitudes when responding to online job offers. The findings also show that fostering a cognitive pause before taking action plays an important role in reducing participants’ tendencies toward impulsive decision-making. Overall, this program demonstrates that concise, structured, and practical digital literacy interventions are effective in enhancing students’ vigilance and self-control in dealing with online fraud risks and have the potential to be replicated in other vocational education contexts. ABSTRAK Maraknya penipuan lowongan kerja daring menjadi tantangan serius bagi siswa sekolah menengah kejuruan yang berada pada fase transisi menuju dunia kerja. Kegiatan Pengabdian kepada Masyarakat (PkM) ini bertujuan untuk memperkuat literasi digital siswa SMK Negeri 5 Kota Bekasi agar mampu mengenali dan mencegah modus penipuan lowongan kerja palsu secara mandiri. Program dilaksanakan melalui workshop interaktif berbasis studi kasus dan simulasi verifikasi, dengan evaluasi menggunakan desain pra dan pasca kegiatan untuk menilai perubahan pengetahuan, keyakinan diri, dan keterampilan verifikasi peserta. Hasil kegiatan menunjukkan adanya peningkatan pemahaman siswa terhadap indikator risiko penipuan, kewajaran prosedur rekrutmen, serta pentingnya perlindungan data pribadi, disertai dengan tumbuhnya sikap lebih berhati-hati dalam merespon tawaran kerja daring. Temuan ini juga menunjukkan bahwa pembiasaan jeda kognitif sebelum bertindak berperan penting dalam mengurangi kecenderungan pengambilan keputusan impulsif pada peserta. Secara keseluruhan, kegiatan ini membuktikan bahwa intervensi literasi digital yang ringkas, terstruktur, dan aplikatif efektif dalam meningkatkan kewaspadaan serta kontrol diri siswa dalam menghadapi risiko penipuan di ruang digital, sekaligus berpotensi direplikasi pada konteks pendidikan vokasi lainnya.